Wind effect on grooved and scallop domes. (1st October 2017) - Sadeghi, Hossein; Heristchian, Mahmoud; Aziminejad, Armin; Nooshin, Hoshyar
Highlights: Wind effect on grooved and scallop domes are studied. A groove on a spherical dome causes abrupt change on the wind pressure. The groove with position angle 90° to wind direction has highest effect. Equations for wind pressure on spherical, grooved and scallop domes are developed. Abstract: This paper numerically studies the wind effect on grooved and scallop domes. The introduction of a groove on a spherical dome causes abrupt change on its wind pressure coefficient (Cp) in the vicinity of the groove. The sharpness of indentation varies with the position angle of the axis of the groove to wind direction and obtains its highest effect at 90°. This paper develops equations for the distribution of Cp on the surface of spherical, grooved and scallop domes with rise to span ratios [0, 0.7]. The results of the equations agree reasonably well with that of CFD.